A 10‐year audit of pregnancies affected by diabetic ketoacidosis at the Pretoria Academic Complex. Issue 3 (31st January 2022) - Maseko, Ncamsile F.; van Zyl, Danie; Adam, Sumaiya
Abstract: Background: Diabetic ketoacidosis (DKA) during pregnancy is associated with increased rates of maternal and perinatal mortality and morbidity. DKA management guidelines are designed to ensure optimal management and minimize adverse outcomes. Objective: To determine the level of adherence to DKA management guidelines at a tertiary center in Pretoria, South Africa and report on maternal and perinatal outcomes of the pregnancies complicated by DKA. Methods: This was a retrospective clinical record audit using the Society for Endocrinology, Metabolism and Diabetes of South Africa guidelines against documented management. Adherence to three cornerstones of therapy was measured: intravenous fluids, insulin therapy, and management of electrolytes. Results: Fifty‐six records of pregnancies that were complicated with DKA over a 10‐year period were reviewed. Mean age was 29.6 years (range 20–43 years). Thirty‐six (64.3%) women had type 1 diabetes mellitus. DKA was categorized into mild ( n  = 26, 46.4%), moderate ( n  = 22, 39.3%), and severe ( n  = 8, 14.3%). The study demonstrated lack of adherence to the three cornerstones of therapy. Of the 49 (85.7%) women with recorded perinatal outcomes, 30.6% had stillbirths. Severe maternal DKA (pH <7.0) demonstrated adverse perinatal outcomes ( P  = 0.005). Conclusion: Despite the availability of guidelines, DKA is sub‐optimally managed in pregnancy, which may contribute to adverse maternal and perinatal outcomes. Abstract : Despite the availability of guidelines, diabetic ketoacidosis is sub‐optimally managed in pregnancy, which may contribute to adverse maternal and perinatal outcomes.